Beeltenissen : 33 zelfportretten van Gentenaars in de lege nissen van het Stadhuis van Gent. (Gent : Stadhuis (org. Barbabelge), 1996)
Anthonis, Johan ; Boon, Elke ; Cassiers, Paul ; Champagne, Carmen ; Cox, Wouter ; Smith, Mario De Brabandere & Alan ; De Brabanter, Walter ; De Buck, Walter ; Deconinck, Lieven ; De Dauw, Walter ; De Lille, Nancy ; Bracke, Kitty De Preeuw & Ann ; De Smet, Stief ; De Taey, Lydie ; Heiremans, Ronny ; Joosten, Diego ; Knobbel ; Lein, Peter ; Loeckx, Heidi ; Louncke, Johan ; Meirlaen, Herman ; Moska ; Nys, Sophie ; Prové, Erika ; Saelens, Sint-Jorishof & Hugo ; Colman, Sint-Juliaan & Martine ; Soenen, Rik ; Spie, Merlin ; Timmerman, Guy ; Theunissen, Jean-Paul ; Tonnard, Philippe ; Van Billemont, Gerry ; Vandecatsije, Bernadette ; Van Werde, Dion ; Verhaeghe, Tine
Nederlands
boek